"Die Fremde ist nicht Heimat geworden, aber die Heimat Fremde."(Alfred Polgar)- Überlegungen zum Jahr des interkulturellen Dialogs 2008 - Wolting, Stephan (Wydawnictwo Naukowe UAM, 2008)
The present article tries to attract attention to the connection between the idea of the European Commision to create in 2008 a Year of the interculturaal dialogue and empiric studies in researching of being abroad. It will be one of the most important purposes in future to develop the studies in intercultural communications in the premise of consulting, coaching and mediation for foreign assignment or a deployment abroad. In this fields there's no doubt that there's a need for focussing new researches on the public and private life of employers abroad or on that what's called the working migration.
Keywords: Fremde; Heimat